Optimizing Resource Allocation in Management Through Advanced Business Analytics - Ali, Md. Mokshud; Nobi, Md. Nur; Uddin , Md. Nasim; Moni, Sharmin Akter; Sultana, Shirin; Ishmam, Md. Rafid (ADPEBI Publisher, 2025)
Allocating resources optimally is crucial for businesses aiming for both strategic and operational success in the complicated and cutthroat business environment of today. By converting data into usable insights, advanced business analytics (ABA) provides useful techniques and tools that improve decision-making. The purpose of this study is to examine how well ABA optimizes resource allocation, highlighting its contribution to increased operational performance and tackling the difficulties encountered in dynamic contexts. To learn more about the use and effects of ABA, the study uses a qualitative research methodology based on secondary sources, examining case studies, industry reports, and existing literature. The underutilization of ABA in businesses as a result of obstacles including a shortage of qualified staff, poor data quality, and change aversion, is the main topic addressed. Important conclusions show that firms that successfully use ABA benefit from better decision-making, more agility, and more efficient use of resources. However, the broad use of analytics is constrained by ongoing issues with data governance and cultural resistance. One of the study's shortcomings is its dependence on secondary data, which might not fully represent the range of organizational experiences with ABA. However, the results have important theoretical and practical ramifications, indicating that to properly utilize advanced business analytics, firms need to make investments in training, data quality enhancements, and cultural change. This study adds to the expanding corpus of research on ABA and offers practitioners practical advice for improving resource management techniques.